1988
DOI: 10.1104/pp.88.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dark Pretreatment on the Kinetics of Response of Barley Pulvini to Gravistimulation and Hormones

Abstract: Starch in pulvinus amyloplasts of barley (Hordeum vulgare cv Larker) disappears when 45-day-old, light-grown plants are given 5 days of continuous darkness. The effect of this loss on the pulvinus graviresponse was evaluated by following changes in the kinetics of response during the 5-day dark period. Over 5 days of dark pretreatment, the lag to initial graviresponse and the subsequent half-time to maximum steady state bending rate increased significantly while the maximum bending rate did not change. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…They also found that about 32% of the pulvinar cell wall material was cellulose, a value quite similar to that reported here (about 35%) derived using an alternative extraction method and measuring incorporation of label rather than absolute amount. In the present work, enhanced cell wall synthesis and elongation of the lower half of gravistimulated pulvini were both initiated between 3 and 6 h. This is significantly later than the 0.5 to 1 h time of initiation of bending found with 80-mm segments used by others (Kaufman and Dayanandan, 1985;Brock and Kaufman, 1988b). Unfortunately, accurate measurement of the initiation of bending was not possible with the relatively short 10-mm segments used here; therefore, the results are not strictly comparable.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…They also found that about 32% of the pulvinar cell wall material was cellulose, a value quite similar to that reported here (about 35%) derived using an alternative extraction method and measuring incorporation of label rather than absolute amount. In the present work, enhanced cell wall synthesis and elongation of the lower half of gravistimulated pulvini were both initiated between 3 and 6 h. This is significantly later than the 0.5 to 1 h time of initiation of bending found with 80-mm segments used by others (Kaufman and Dayanandan, 1985;Brock and Kaufman, 1988b). Unfortunately, accurate measurement of the initiation of bending was not possible with the relatively short 10-mm segments used here; therefore, the results are not strictly comparable.…”
Section: Discussioncontrasting
confidence: 47%
“…Other workers (Kaufman and Dayanandan, 1985;Brock and Kaufman, 1988b), using 80-mm Avena segments to study the response of the pulvinus to gravity, have reported the initiation of bending by 0.5 to 1 h. Although preliminary experiments also showed significant gravistimulated bending of the 10-mm segments used here, this response was difficult to measure accurately, especially at early times, because the segments were so short. Therefore, elongation of the lower half of gravistimulated pulvini was chosen as an alternative method to determine the kinetics of the pulvinar growth response.…”
Section: Kinetics Of Cravistimulated Pulvinar Crowthmentioning
confidence: 53%
See 3 more Smart Citations